Cinnamyl Schiff bases: synthesis, cytotoxic effects and antifungal activity of clinical interest. (10th August 2020) - Magalhães, T.F.F.; da Silva, C.M.; dos Santos, L.B.F.; Santos, D.A.; Silva, L.M.; Fuchs, B.B.; Mylonakis, E.; Martins, C.V.B.; de Resende‐Stoianoff, M.A.; de Fátima, Â.
Abstract: The aim of this study was to synthesize and investigate the in vitro antifungal properties of 23 cinnamyl Schiff bases. In addition, cytotoxic effects of such cinnamyl Schiff bases against human lung, kidney or red blood cells were also checked. The compounds were synthesized in a single‐step, 2 min of reaction under microwave irradiation produced up to 97% yield. Six of the 23 cinnamyl Schiff bases possessed antifungal activities against strains of Candida, Aspergillus, Fonsecaea and, particularly, Cryptococcus species. Indeed, cinnamyl Schiff bases 1 and 23 exhibited minimum inhibitory concentration (MIC) values more than twofold lower than fluconazole (FCZ) against all the Cryptococcus neoformans strains (MIC = 1·33, 1·4 and 5·2 µg ml −1, respectively) and Cryptococcus gattii strains (MIC = 5·3, 2·8 and 9·2 µg ml −1, respectively) (12 strains of each species) while cinnamyl Schiff base 11 was as potent as FCZ against all strains from both Cryptococcus species. No significant cytotoxic effects were observed for Schiff bases against human lung, kidney or red blood cells, all presenting selective indexes higher than 10. In conclusion, this study revealed cinnamyl Schiff bases, especially 1 and 23, as new lead anticryptococcal agents for the discovery of novel antifungal drugs. Significance and Impact of the Study: The occurrence and severity of fungal infections have increased in recent decades due to resistance to available antifungal drugs and the appearance of new emerging pathogens. Thus, the search for new antifungal agents is mandatory. From a series of 23 cinnamyl Schiff bases, two compounds (1 and 23 ) were interrogated as new anticryptococcal agents without significant cytotoxicity against human lung, kidney or red blood cells. In turns, these new Schiff bases are lead compounds for the discovery of novel antifungal drugs. Abstract : Significance and Impact of the Study: The occurrence and severity of fungal infections have increased in recent decades due to resistance to available antifungal drugs and the appearance of new emerging pathogens. Thus, the search for new antifungal agents is mandatory. From a series of 23 cinnamyl Schiff bases, two compounds (1 and 23 ) were interrogated as new anticryptococcal agents without significant cytotoxicity against human lung, kidney or red blood cells. In turns, these new Schiff bases are lead compounds for the discovery of novel antifungal drugs.